Word and non-word spans across neurotypical adults: A cross-sectional comparative study. - Shree, Keerrthana; Jahnavi, A.; Abhishek, B. P.; Jain, Pranjal (Journal of the All India Institute of Speech & Hearing)
Purpose: Memory span tasks are critical assessment paradigms for evaluating phonological short-term memory and word and non-word spans across different populations. Understanding how word and non-word spans evolve across adulthood helps refine working memory models and establish age-specific normative standards for clinical assessment. Therefore, the current study aimed to compute and compare word and non-word spans across four age groups of neuro-typical Kannada-speaking adults. Materials and Methods: A total of 80 participants (20 per age group) were recruited across four different age groups (18–30, 31–40, 41–50, and 51–60 years). The test stimuli included semantically related and unrelated word lists, and a non-word list with varied syllable length. The stimuli were presented auditorily, and participants recalled and produced them in the same order (serial recall). The word and non-word spans were determined by the maximum length at which participants correctly recalled two out of three trials. The responses were subjected to descriptive analysis, followed by nonparametric tests (Kruskal–Wallis H test and Mann–Whitney U test). Result: A progressive decline in word and non-word spans was observed with advancing age. The youngest group (18–30 years) demonstrated significantly higher scores for both semantically unrelated and related (median = 4.00; P < 0.001) as well as non-word types compared with older age groups. Conclusions: The current study findings provide empirical evidence of age-related decline in both word and non-word spans, contributing to the theoretical refinement of working memory models and establishing age-specific normative data essential for clinical assessment and early detection of cognitive decline.